2020
DOI: 10.2147/nss.s273129
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Tongue Position is a Risk Factor for Upper Airway Concentric Collapse in Obstructive Sleep Apnea: Observation Through Sleep Endoscopy</p>

Abstract: Identification of upper airway (UA) obstruction based on pharyngeal factors is important for obstructive sleep apnea (OSA) evaluation. This study is to assess the association between UA collapse characteristics and Friedman tongue position (FTP) in patients with OSA through drug-induced sleep endoscopy (DISE). Patients and Methods: Retrospective study in individuals with OSA who were intolerant to continuous positive airway pressure (CPAP) treatment, submitted to DISE between June 1, 2013, and July 31, 2017. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Twenty-two patients (91.7%) had a high tongue position (FTP IV) in the current study, as well as many complete concentric collapses. A recent study identified a positive correlation between higher tongue position and complete concentric collapse, which may elucidate the findings of this study ( 33 ).…”
Section: Discussionsupporting
confidence: 82%
“…Twenty-two patients (91.7%) had a high tongue position (FTP IV) in the current study, as well as many complete concentric collapses. A recent study identified a positive correlation between higher tongue position and complete concentric collapse, which may elucidate the findings of this study ( 33 ).…”
Section: Discussionsupporting
confidence: 82%
“…Given the poor prognosis that having a CCC implies, an attempt has been made to search for predictors of its presence. FTP grade IV has been highly correlated with CCC [28] with up to a 4.4-fold higher risk of having CCC than grade I individuals. A recent study by Thuler et al [29] showed a more significant presence of CCC in patients with transverse maxillary deficiency, mainly when the intermolar distance was less than 27.5 mm.…”
Section: Discussionmentioning
confidence: 98%
“…For internists, the evaluation of UA characteristics may have significance for OSA precision treatment, classification, prediction of CPAP treatment pressure, and treatment compliance (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Tonsils were classified according to their size as grades I, II, and III. Tonsil size is usually classified into grades 0-4 (19,20). In this study, for simplicity, we classified the tonsil size into the following three grades: grade 1 (defined as tonsils absent or tonsils hidden inside the pillars or tonsils extending to the pillars), grade 2 (defined as tonsils extending beyond the pillars), and grade 3 (defined as tonsils extending to the midline).…”
Section: Data Collection and Definitionmentioning
confidence: 99%